2019
DOI: 10.1016/j.ecss.2018.12.021
|View full text |Cite|
|
Sign up to set email alerts
|

Mangroves of Vietnam: Historical development, current state of research and future threats

Abstract: Vietnamese mangroves are among the most productive & biologically important ecosystems of the world; providing habitat/nursing grounds for commercial & non-commercial fish species, food, medicine, building materials/fuel for local communities, as well as carbon storage (blue carbon) & coastal protection from storm events. However, Vietnam's mangroves have been lost in recent decades (~38%) or degraded, predominantly driven by herbicides during the Vietnam War and later by conversion to aquaculture and coastal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
73
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 116 publications
(74 citation statements)
references
References 157 publications
0
73
0
1
Order By: Relevance
“…The dry season begins in April and ends in November of the following year, whereas the rainy season occurs between May and October. The average temperature is approximately 26 • C, the annual rainfall is roughly 1300-1400 mm, and the relative humidity is approximately 80% [35]. This district is well-known for its mangrove reforestation and rehabilitation programs, not only in Vietnam but also throughout Southeast Asia [36].…”
Section: Study Areamentioning
confidence: 99%
“…The dry season begins in April and ends in November of the following year, whereas the rainy season occurs between May and October. The average temperature is approximately 26 • C, the annual rainfall is roughly 1300-1400 mm, and the relative humidity is approximately 80% [35]. This district is well-known for its mangrove reforestation and rehabilitation programs, not only in Vietnam but also throughout Southeast Asia [36].…”
Section: Study Areamentioning
confidence: 99%
“…The Mekong delta in Viet Nam (Fig. 1), the third largest delta in the world (Coleman and Huh, 2004), has a particularly well-developed mangrove environment (Veettil et al, 2019). The delta makes up for 12 % of the country's natural land and 19 % of its national population, and hosts a population of 20 million inhabitants (Mekong River Commission, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Following the ravages of the Viet Nam War (1960)(1961)(1962)(1963)(1964)(1965)(1966)(1967)(1968)(1969)(1970)(1971)(1972) on the delta's forests, these important advantages have significantly impacted the mangroves of the delta, notably in the muddy southwestern and Gulf of Thailand areas where large tracts have been removed to provide timber for charcoal and for the construction industry, and to make place for shrimp farms and aquaculture (Phan and Hoang, 1993;Christensen et al, 2008;Veettil et al, 2019). Several recent studies have also shown that erosion is becoming increasingly rampant along much of the delta shoreline (Anthony et al, 2015;Besset et al, 2016;Allison et al, 2017;Li et al, 2017), leading to the recurrent displacement of coastal populations (Boateng, 2012) and increasing recourse to coastal protection structures, notably dykes (Albers and Schmitt, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The country of Vietnam straddles some 13 degrees of latitude with a corresponding long coastline with biodiversity hotspot which are highly threatened 1 – 6 . In particular, mangrove forests which mainly occur in the Mekong Delta along the southern coastline, and also around the Red River Delta in the north, are being destroyed rapidly in spite of their importance to economics, coastal stability, and habitat for organisms 7 – 9 . Within the Mekong Delta, mangrove forests are particularly developed in Ca Mau and Bac Lieu provinces 9 .…”
Section: Introductionmentioning
confidence: 99%
“…In particular, mangrove forests which mainly occur in the Mekong Delta along the southern coastline, and also around the Red River Delta in the north, are being destroyed rapidly in spite of their importance to economics, coastal stability, and habitat for organisms 7 – 9 . Within the Mekong Delta, mangrove forests are particularly developed in Ca Mau and Bac Lieu provinces 9 . Besides these areas, a mangrove belt still covers part of the shoreline in Kien Giang Province also in the Mekong Delta, belonging to Kien Giang Biosphere Reserve, recognized by UNESCO in 2006 10 – 12 .…”
Section: Introductionmentioning
confidence: 99%